RECYCLING AND MANAGEMENT OF MICROPLASTIC WASTE - Geetha Babu; Tamilamuthan.R; Sindhu.J.A (The Bioscan, 2025)
PL pollution is caused by contemporary society's unsustainable consumption and dumping of PL items, placing economies, landscapes, and people's health in risk So far, remediation operations have attempted to mitigate the negative effects of PL pollution, but efforts are still unable to cope with the increased volumes of PL released to the environment. As a consequence, emphasizing a standardized measurement strategy to recycle PL emissions into the environment is essential. Badly run garbage is a significant ground cause of PL pollution that could be reduced by changing life of PLs, especially in terms of production, usage, and destruction, with an Effective Waste Management System. In this review article, we describe existing techniques for improving the life span and waste disposal of PLs that may be applied to decrease PL waste and environmental and health implications. (1) Regulatory oversight of manufacturing and utilization; (2) eco-design; (3) rising the demand for recycled PLs; (4) lowering the use of PL products; (5) use of renewable power for reprocessing; (6) extended producer responsibility over waste; (7) advancements in collection systems; (8) good planning of composting; (9) utilisation organic and degradable PL products; and (10) advancement in recyclability are among the ten suggestions for decision makers to reduce its environmental footprint.